2015
DOI: 10.1590/2237-6089-2015-0009
|View full text |Cite|
|
Sign up to set email alerts
|

Association between inaccurate estimation of body size and obesity in schoolchildren

Abstract: Objectives: To investigate the prevalence of inaccurate estimation of own body size among Brazilian schoolchildren of both sexes aged 7-10 years, and to test whether overweight/obesity; excess body fat and central obesity are associated with inaccuracy. Methods: Accuracy of body size estimation was assessed using the Figure Rating Scale for Brazilian Children. Multinomial logistic regression was used to analyze associations. Results: The overall prevalence of inaccurate body size estimation was 76%, with 34% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
12
0
3
Order By: Relevance
“…Table 1 presents a detailed description of the main studies found in this review. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 The following were highlighted: authors; country; year of publication; method employed; characteristics of the sample; size of the assessed body image; and evaluation instrument used. It should be noted that a sample size varied from 25 to 11,466 children.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 presents a detailed description of the main studies found in this review. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 The following were highlighted: authors; country; year of publication; method employed; characteristics of the sample; size of the assessed body image; and evaluation instrument used. It should be noted that a sample size varied from 25 to 11,466 children.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies were carried out to verify the accuracy in the judgment of body dimensions of children. Costa et al 13 and Ling et al 16 found prevalence of high inaccuracy in Brazilian and Chinese children, respectively. According to Costa et al, 13 most of them overestimated their body size.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations